Evaluation of the protective role of vitamin C in imidacloprid-induced hepatotoxicity in male Albino rats - Soujanya, S. (Medknow Publications & Media Pvt Ltd, 2013)
In the present study, the effects of oral administration of imidacloprid for 4 weeks on serum biochemical, oxidative stress, histopathological and ultrastructural alterations were assessed in the liver of male rats. This study also aimed to investigate whether vitamin C could protect against the imidacloprid-induced oxidative stress. Forty-eight male Sprague dawley rats were divided into four groups of 12 animals each. Group 1 served as the control, while groups 2 and 4 were administered with imidacloprid (80 mg/kg body weight) daily by oral gavage for 28 days. In addition to imidacloprid, group 4 also received vitamin C at 10 mg/kg daily by oral gavage for 28 days. Group 3 was maintained as the vitamin C control (dose as above). The serum biochemical assays revealed a significant (P < 0.05) increase in alanine transaminase and aspartate transaminase and decrease in total protein in group 2. The tissue biochemical profile revealed a significant (P < 0.05) reduction in reduced glutathione concentration in the liver of group 2 animals. Histologically, the liver showed marked dilation, congestion of central vein, portal vein and sinusoidal spaces, vacuolation/fatty change and degenerated hepatocytes. Ultra thin sections of the liver revealed swollen nuclei, varied size and shape of mitochondria, disrupted chromatin and rough endoplasmic reticulum. Co-treatment with vitamin C significantly (P < 0.05) reversed the imidacloprid-induced changes.